7x-9-9x=6x+12

Simple and best practice solution for 7x-9-9x=6x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-9-9x=6x+12 equation:


Simplifying
7x + -9 + -9x = 6x + 12

Reorder the terms:
-9 + 7x + -9x = 6x + 12

Combine like terms: 7x + -9x = -2x
-9 + -2x = 6x + 12

Reorder the terms:
-9 + -2x = 12 + 6x

Solving
-9 + -2x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-9 + -2x + -6x = 12 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-9 + -8x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-9 + -8x = 12 + 0
-9 + -8x = 12

Add '9' to each side of the equation.
-9 + 9 + -8x = 12 + 9

Combine like terms: -9 + 9 = 0
0 + -8x = 12 + 9
-8x = 12 + 9

Combine like terms: 12 + 9 = 21
-8x = 21

Divide each side by '-8'.
x = -2.625

Simplifying
x = -2.625

See similar equations:

| -5A+10=5 | | -2A+1=4 | | 3a+1=2x+4 | | 4=2x-10 | | y=(x-3)(x-3)+(x-9)(x-9) | | 3/4x=7/1 | | 6.5/500= | | -3+A=2 | | 6(7d-12)=30 | | 4n=6.58 | | 28y+4=0 | | z/8-5=5 | | 6-3(x+10)=-5 | | ln(e)=0.3ln(x) | | (X^2-4)(x^2-4)=127449 | | 8x-7=59 | | -A-1=-3 | | 8*m*n*7*m*m*n= | | y=(x+1)(x+3)(x-4) | | (x)(x)+14x=0 | | 3(8+6y)=2(9y-12) | | 8mn*7m*7mn= | | Xsquared+14x+c=0 | | 3x+X=7 | | 4(3x+7)=2(6x+14) | | 7xw*2w= | | -5A=-15 | | 5x+7/2=3x+5/4+2x+3 | | 14+6b+7-2b= | | 6(3x-4)=60 | | 2(y+4)=7(y-1) | | 1-X+X=11 |

Equations solver categories